Jacob Portman’s Identity Confusion in Ransom Riggs’ Miss Peregrine’s Home for Peculiar Children - LINDA LESTIANA (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
This study analyses Jacob Portman’s identity confusion in Ransom Riggs’ Miss Peregrine’s Home for Peculiar Children. Adolescent period, as experienced by Jacob Portman, is considered as the most sensitive and dangerous period in a person’s life because adolescents experience a search of identity in that period. They may discover their self-identity or even experience identity confusion. This study is aimed to explore identity confusion depicted in a fantasy novel, and to reveal the possible factor of the identity confusion which happen to the protagonist character. The data source of the study is Ransom Rick’s fantasy novel, entitled Miss Peregrine’s Home for Peculiar Children. Analysis of the study is done by applying the theoretical concept of Identity confusion by Erik H. Erikson. Identity versus role confusion is part of psychological stages which can help to reveal identity confusion that appears on Jacob Portman. The study showed that Jacob Portman experienced identity confusion, he cannot answer the big question ‘who am I?’. Jacob confuses about who is he and where he belongs in the society. And this study also showed the possible factors that caused Jacob Portman experienced identity confusion. First is caused by lack of supports from his parents, second is his parents always force him to be like they want, for the last possible factors is he does not have enough commitment to decide thing for his own life. So, Jacob cannot successfully through identity versus role confusion stage which cannot bring him to be mature individual as people expect. Keywords: psychological stages, identity vs role confusion, identity, identity confusion